The short-course chemotherapy in the treatment of multiple drug resistant tuberculosis in children with different HIV status - E. Yu. Zorkaltseva; S. V. Pugacheva; L. V. Zaritskaya; D. A. Kudlay (Туберкулез и болезни лёгких)
The objective: to study the time frames and efficacy of treatment for tuberculosis with confirmed and suspected multiple drug resistance (MDR) in children with different HIV status.Subjects and methods. The method of continuous sampling was used in the study which included 21 children with MDR tuberculosis, they all had been exposed to MDR TB and were treated in hospital. 3 children had concurrent HIV.Results. The duration of the intensive care phase in HIV negative children (19 people) made: 60 doses – 1 (5.3%) child, 90 doses – 11 (57.9%) children, 120 doses – 2 (10.5%) children, 180 doses – 3 (15.8%) children, 240 doses – 1 (4.3%) child. The duration of the continuation phase was the following: 120 doses – 1 (4.3%) child, 150 doses – 1 (5.3%) children, 180 doses – 12 (63.1%) children, 270 doses – 1 (5.3%) children, 320 doses – 3 (15.8%) children.The duration of the intensive phase of treatment in 3 children with concurrent MDR TB and HIV infection made 180 doses in 2 (66.6%) children and 240 doses in 1 (33.4%) child. The continuation phase included 180 doses in 2 (66.6%) children and 320 in 1 (33.4%) child respectively.Outcomes of the main course of chemotherapy were favorable in the majority of the cases - inflammatory changes resolved, focuses consolidated and fibrosis formed in the lung tissue.Conclusion. Should children have negative results of sputum tests, the treatment is prescribed based on the results of drug susceptibility tests of the index case. If limited tuberculous lesions are diagnosed, the duration of treatment of children with MDR can be shorter. The outcomes of short-course treatment in children with tuberculosis are favorable, changes in the lungs have resolved and thickened more frequently. In children with HIV infection, low adherence to HIV treatment in socially disadvantaged families requires long-term directly observed tuberculosis chemotherapy combined with antiretroviral therapy.